2019
DOI: 10.3390/cancers11040547
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights of Lymphomagenesis of Helicobacter pylori-Dependent Gastric Mucosa-Associated Lymphoid Tissue Lymphoma

Abstract: Gastric mucosa-associated lymphoid tissue (MALT) lymphoma is the most common subtype of gastric lymphoma. Most gastric MALT lymphomas are characterized by their association with the Helicobacter pylori (HP) infection and are cured by first-line HP eradication therapy (HPE). Several studies have been conducted to investigate why most gastric MALT lymphomas remain localized, are dependent on HP infection, and show HP-specific intratumoral T-cells (e.g., CD40-mediated signaling, T-helper-2 (Th2)-type cytokines, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 136 publications
(210 reference statements)
1
37
0
2
Order By: Relevance
“…As previous studies have suggested that H. pylori cytotoxin-associated gene A (CagA) directly participate to the lymphomagenesis of H. pylori -dependent GML [75,76,77], it could also be of major interest to determine if CagA could participate in the deregulation of these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have suggested that H. pylori cytotoxin-associated gene A (CagA) directly participate to the lymphomagenesis of H. pylori -dependent GML [75,76,77], it could also be of major interest to determine if CagA could participate in the deregulation of these miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current concept, MALT lymphomagenesis is mediated via a multi‐step sequence initiated by H. pylori infection‐associated development of acquired MALT in the gastric mucosa accompanied by invasion of immune effector cells and downstream increased production of pro‐inflammatory mediators 16‐20 . Importantly, H. pylori is not able to directly stimulate B‐cells, and thus differentiation and accrual of H. pylori reactive T‐cells (mostly T H2 and T regs ) followed by persistent antigenic stimulation play a crucial role in this process and are mainly responsible for the perpetual activation of the marginal zone B‐cells eventually triggering the switch from polyclonal to monoclonal expansion 16,17,21,22 . This assumption has been underlined by studies showing that successful cultivation of lymphoma cells is only possible in co‐culture of H. pylori specific T‐cells, while the lymphoma cells decline and express less interleukins (IL) if deprived of H. pylori specific T‐cells 16,22 .…”
Section: Rationales For Immunomodulatory Treatment In Malt Lymphomamentioning
confidence: 99%
“…When the pathogen is eradicated by antibiotic treatment, MALT lymphoma regresses in over 75% of cases, suggesting that continuous presence of the bacteria is required to maintain malignancy potential [13,14]. In addition, eradication of the pathogen significantly reduces the chance of recurring gastritis and peptic ulceration [15,16]. According to 2018 estimates by the World Health Organization (WHO) and Global Burden of Cancer Study (GLOBOCAN), gastric cancer is the third leading cause of annual deaths due to cancer worldwide [17].…”
Section: Introductionmentioning
confidence: 99%